Implementasi Algoritma C4.5 Untuk Mengukur Tingkat Kepuasan BPJS Keternaga Kerjaan - Afifah (Jurnal Sains dan Teknologi, 2021)
BPJS Employment (Managing Social Security Agency) is a form of public service. Efforts in improving services need to have benchmarks on the level of participant satisfaction both in terms of tangibles, reliability. Responsiveness, assurance and empathy. Based on the research and the problem, a research about participant satisfaction was conducted. Participants are given a questionnaire which will be processed using the C45 algorithm. For this reason, it is necessary to evaluate the participant's side to find out whether the participant is satisfied or not satisfied with the services provided. Seeing the problems above, a research will be conducted with the title "Data mining to measure the level of satisfaction of BPJS Employee participants using the C45 algorithm". The purpose of this study is to find out whether BPJS Employment has provided quality services that are in line with participants' expectations.